Short Communication: A Descriptive Analysis of Dried Blood Spot Adherence Testing Among Ugandans with HIV Presenting with Cryptococcal Meningitis - Lofgren, Sarah M; Nicol, Melanie R; Kandole, Tadeo K; Castillo-Mancilla, Jose; Anderson, Peter L; Mpoza, Edward; Tugume, Lillian; Bangdiwala, Ananta S; Ssebambulidde, Kenneth; Hullsiek, Katherine Huppler; Rhein, Joshua; Meya, David B; et al. (AIDS research and human retroviruses, 2021)
Early antiretroviral therapy (ART) initiation after cryptococcal meningitis increases mortality, and those unmasking cryptococcosis after <2 weeks of ART have higher mortality. However, it is unknown if those presenting as ART experienced are actually adherent to their ART. Unknowingly, restarting ART in persons, who have discontinued ART, may be a fatal iatrogenic error. To evaluate ART adherence in an exploratory analysis, we collected dried blood spots on 44 HIV-infected persons presenting with cryptococcal meningitis. We quantified tenofovir diphosphate (TFV-DP) and lamivudine (3TC) from dried blood spots. We quantified cumulative ART adherence over the preceding 6-8 weeks based on TFV-DP concentrations and adherence over the last few days based on 3TC concentrations. Of 22 ART experienced, 20 (91%) had quantifiable concentrations. Of 18 receiving tenofovir, 15 (83%) had TFV-DP consistent with drug intake of ≥4 doses/week or moderate adherence. With 3TC, 72% (18/22) had detectable levels consistent with adherence over the last 3 days before measurement. Only three ART-experienced subjects were alive and virally suppressed at 4 months ( = 2 on ART for <30 days; = 1 with undetectable antiretrovirals). Surprisingly, of 22 who reported not receiving ART, 4 (18%) had quantifiable tenofovir. Most ART-experienced subjects were taking their ART with moderate to good adherence with the majority likely having viral resistance given generally at good ART levels, receipt of intensive adherence counseling, and lack of subsequent viral suppression. The World Health Organization (WHO) guidelines recommend adherence counseling with ART continuation and repeat viral loads in 1-3 months before switching to second-line ART. These recommendations are likely inappropriate in those with central nervous system infections given the additional possible harm of central nervous system immune reconstitution syndrome. Further study to evaluate continuation of ART regimens when presenting with cryptococcosis has benefit, with checking blood levels at presentation potentially being a helpful option. ClinicalTrials.gov Identifier: NCT01802385.